2007
DOI: 10.1093/jn/137.4.953
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Inhibitory Peptides from a Lactotripeptide-Enriched Milk Beverage Are Absorbed Intact into the Circulation1

Abstract: Food products containing angiotensin converting enzyme (ACE) inhibitory peptides reportedly play a role in treatment of mild hypertension. The aim of this placebo-controlled crossover study was to assess the bioavailability of Ile-Pro-Pro and 7 other ACE-inhibiting peptides present in a lactotripeptide (LTP)-enriched yogurt beverage and whether meal intake affects Ile-Pro-Pro bioavailability. Six male and female subjects randomly consumed an LTP-enriched yogurt beverage or a placebo in the fasted state and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(199 citation statements)
references
References 38 publications
5
192
1
1
Order By: Relevance
“…However, in human studies the concentration of VPP and IPP in the products does not seem to correlate with the reduction in BP. 26 The influence of enzymatic digestion on the concentration of lactotripeptides is widely unknown and plasma concentration of VPP and IPP did not increase to an extent compatible with an antihypertensive effect after giving six healthy subjects FM in a study by Foltz et al 27 Only a modest increase of IPP was evident, whereas the concentration of VPP remained unchanged. Non-FM also increased the plasma concentration of IPP, thereby suggesting that this happens by the hydrolysis of milk proteins during digestion.…”
Section: Discussionmentioning
confidence: 97%
“…However, in human studies the concentration of VPP and IPP in the products does not seem to correlate with the reduction in BP. 26 The influence of enzymatic digestion on the concentration of lactotripeptides is widely unknown and plasma concentration of VPP and IPP did not increase to an extent compatible with an antihypertensive effect after giving six healthy subjects FM in a study by Foltz et al 27 Only a modest increase of IPP was evident, whereas the concentration of VPP remained unchanged. Non-FM also increased the plasma concentration of IPP, thereby suggesting that this happens by the hydrolysis of milk proteins during digestion.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, in a recent placebo-controlled trial in 135 mildly hypertensive subjects by Engberink et al no effects of milk-derived peptides on blood pressure, ACE activity or plasma angiotensin II concentrations were found after 8 weeks of treatment (64) . Also, bioavailability of these peptides is questionable (58) , although one study has demonstrated the uptake of intact lactotripeptides (65) . Finally, the amount of Dairy consumption and the metabolic syndromeACE-inhibitory peptides in non-enriched dairy products may simply be too low to play a significant role in blood pressure regulation.…”
Section: Effects Of Bioactive Peptides On Blood Pressure and Coagulationmentioning
confidence: 99%
“…Milk-derived peptides improve vascular response in vitro probably through stimulation of endothelial nitric oxide (NO) release (Sipola et al, 2002b). It has been shown in experimental and clinical trials that the tripeptides Ile-Pro-Pro and Val-Pro-Pro can be absorbed at least partly from the intestine (Foltz et al, 2007;Jauhiainen et al, 2007b). Blood pressure-lowering effects of milk products containing Ile-Pro-Pro and Val-Pro-Pro tripeptides have been shown in several clinical trials (Seppo et al, 2003;Jauhiainen et al, 2005) and a meta-analysis of 12 randomized controlled trials found that the ingestion of tripeptides Ile-Pro-Pro and Val-Pro-Pro for 4-21 weeks decreases systolic blood pressure by 4.8 mm Hg and diastolic blood pressure by 2.2 mm Hg (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%